Simulations of thermoelastic triangular cell lattices with bonded joints by finite element analysis. (April 2017) - Ha, Chan Soo; Plesha, Michael E.; Lakes, Roderic S.
Abstract: Thermoelastic triangular cell lattices composed of bi-material curved ribs were designed and analyzed by finite element simulation. Positive, negative, or zero thermal expansion was possible by varying rib curvature if joints can pivot freely, as expected. Welded or bonded joints result in nonzero expansion but smaller in magnitude than that of a constituent material having higher thermal expansion coefficient. The effects of rib curvature variation for bonded joints were found to be negligible. Rib slenderness for both joints did not influence the coefficient of thermal expansion. We present a square lattice with bonded joints that has zero net thermal expansion; each curved bi-material rib has zero expansion.